Detailed report on the virtual workshop on water footprint in livestock systems - Gonzalez Quintero, Ricardo; Mwema, Emmanuel; Isiaho, Glarion; Dao, Hang; Van Der Hoek, Rein; Notenbaert, An (2024)
The virtual workshop on the water footprint in livestock systems, held on July 10, 2024, brought together experts from various institutions to discuss methodologies, tools, and challenges related to assessing water usage in livestock systems. Key topics included the use of tools like CLEANED for environmental assessment, the complexities of water allocation in livestock feed production, and the environmental impacts of livestock systems on water quality. This report provides an in-depth overview of the discussions, insights, and recommendations from the workshop.